Developing Algorithm for Security System in Smart Door Lock and Fire Extinguishing Spray System Utilizing the CtrlX Platform - Yuliadi Erdani; Mochammad Naufal; Muhammad Giriarda Abrari; Herman Budi Harja; Achmad Sambas; Siti Aminah (Informatik : Jurnal Ilmu Komputer, 2026)
Industries face high risks from unauthorized access and fire hazards, necessitating reliable and responsive safety systems. This research presents the design and evaluation of an IIoT-based smart door lock and fire extinguishing system utilizing the CtrlX Automation platform. The system integrates RFID and fingerprint-based access control with temperature, gas, and flame sensors supported by edge-AI processing. Experimental results from 12 trials demonstrated an average fire detection time of 344.25 ms, smoke detection accuracy of 92.21%, sprinkler actuation delay of 515.58 ms, evacuation door unlocking time of 811.50 ms, and cloud log reliability of 99.70%, with a 14.42% reduction in false alarms. Extended scenarios using various fire sources (paper, plastic, oil), sensing distances (1–3 m), and environmental interferences (airflow, smoke particles) confirmed the robustness of the system. Communication security was validated using MQTT over TLS with AES encryption, resulting in a latency overhead of only 8 ms, while the IDS demonstrated 96.2% detection accuracy against simulated DoS attacks. These findings indicate that the proposed system achieves fast detection, high accuracy, and reliable communication compared to conventional systems, thereby enhancing industrial and smart building safety.